Caddisfly Silk-Polycaprolactone Foams: Physicochemical and Biological Properties of Nature-Inspired Biomaterials - Mateusz M. Urbaniak; Mariusz Tszydel; Konrad Szustakiewicz; Aleksandra Szwed-Georgiou; Bartłomiej Kryszak; Marcin Włodarczyk; Sylwia Michlewska; Piotr Jóźwiak; Tomislav Ivankovic; Mikołaj K. Cybulski; Karolina Rudnicka (Journal of Functional Biomaterials, 2025)
The unique properties of insect silk have attracted attention for years to develop scaffolds for tissue engineering. Combining natural silks with synthetic polymers may benefit biocompatibility, mechanical strength, and elasticity. Silk-modified biomaterials are a promising choice for tissue engineering due to their versatility, biocompatibility, and many processing methods. This study investigated the physicochemical and biological properties of biocomposites formed by combining caddisfly silk (Hydropsyche angustipennis) and polycaprolactone (PCL). The PCL foams modified with caddisfly silk demonstrated full cytocompatibility and enhanced fibroblast adhesion and proliferation compared to unmodified PCL. These silk-modified PCL foams also induced NF-κB signaling, which is crucial for initiating tissue regeneration. Notably, the antimicrobial properties of the silk-modified PCL foams remained consistent with those of unmodified PCL, suggesting that the addition of silk did not alter this aspect of performance. The findings suggest that caddisfly silk-modified PCL foams present a promising solution for future medical and dental applications, emphasizing the potential of alternative silk sources in tissue engineering.